Basic cell Culture Protocols. - Helgason, Cheryl D; Ed. Miller, Cindy L; Ed
At some point in their careers, virtually every scientist and technician, as well as many medical professionals, regardless of their area of specialization have a need to utilize cell culture systems. Updating and significantly expanding upon the previous editions, Basic Cell Culture Protocols, Fourth Edition provides the novice cell culturist with sufficient information to perform the basic techniques, to ensure the health and identity of their cell lines, and to be able to isolate and culture specialized primary cell types. The intent of this extensive volume is to generate a valuable resource containing clear methodologies pertinent to current areas of investigation, rather than attempting to educate cell culturists on specific cell types or organ systems. Written in the highly successful Methods in Molecular Biology, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Comprehensive and up-to-date, Basic Cell Culture Protocols, Fourth Edition compiles the essential techniques needed to approach this vital laboratory activity with full success.